Minimum Wages, Unemployment and Informality: Evidence from Panel Data on Russian Regions - Alexander Muravyev; Aleksey Oshchepkov (Institute for the Study of Labor (IZA), 2013)
This paper revisits labor market effects of the minimum wage by taking advantage of a unique institutional setting and rich data from Russia that cover 89 regions over 10 years, from 2001 to 2010. Our empirical analysis draws on the methodology introduced by Neumark and Wascher, in which labor market outcomes at the regional level are related to the relative minimum wage (captured by the Kaitz index) in a panel setting. We find that the minimum wage raises unemployment among young workers aged 15 to 24. In contrast, there is no evidence of disemployment effects of the minimum wage for workers aged 25-72, including women. In addition, minimum wage hikes are associated with an increase in informal employment.
Keywords: J38; J23; 330; minimum wages; unemployment; informal employment; Russia